Pengaruh Content Marketing dan Influencer Marketing terhadap Purchase Intention Produk Somethinc Pada Generasi Z Pengguna Tiktok di Blitar - Maharani, Nabella Intan Kiki; Kurniawan, Moh Zaki; Mawardi, Muhammad Adib; Khoirianto, Redy (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the Influence of Content Marketing and Influencer Marketing on Purchase Intention of Somethinc Products on Generation Z Tiktok Users in Blitar. This study uses a quantitative method, with primary data in the form of questionnaire answers distributed online using Google Form to respondents. The population in this study was Generation Z users of Somethinc products who were active on Tiktok, with a sample of 100 respondents using the Lemeshow formula. Data was processed and retrieved using SPSS version 21. The results of the study indicate that: 1) Content marketing has a significant partial influence on the purchase intention of somethinc products on generation z TikTok users in Blitar; 2) Influencer marketing has a significant partial influence on the purchase intention of somethinc products on generation z TikTok users in Blitar; 3) Content marketing and influencer marketing have a significant influence together on the purchase intention of somethinc products on generation z TikTok users in Blitar.